Pengukuran Efektivitas Jumlah Pembaca dan Pendanaan Taman bacaan Berbasis CIPP dalam Meningkatkan Minat Baca di Kabupaten Bogor - Syarifudin Yunus (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
Descriptive qualitative research on the effectiveness of the number of readers and funding of reading parks based on the CIPP (Context, Input, Process, Product) model involved 13 community reading parks in Bogor Regency in increasing reading interest. It concluded that the effectiveness level of reading parks was “fair,” with an average score of 3.56. This means that there is still a gap between expectations and reality in the management of reading parks, which is not yet optimal. Of the 23 aspects evaluated in the four CIPP components, there were five aspects categorized as effective (needs analysis, objectives, targets, organizational structure, benefits), 17 aspects were categorized as sufficient (policy, program, procedures and mechanisms, human resources, supporting facilities, coaching system, goal achievement, planning, implementation and coordination, reporting, socialization, evaluation, community support, achievement of results, impact, development, and reputation), and 1 aspect was categorized as ineffective, namely the budget. The number of reading park readers consists of: 1) more than 60 children reaching 30%, 2) between 30-60 children reaching 30%, and 3) less than 30 children reaching 40%. In terms of funding, the sources of funding for reading parks are a) own funds or self-help reaching 75%, b) CSR (corporate social responsibility) reaching 15%, and c) private donors reaching 10%, while reading parks with a collection of less than 3,000 books reach 85% of reading parks and those with more than 10,000 books reach 15% of reading parks.